Prevalence and morphometric analysis of three-rooted mandibular first molars in a Brazilian subpopulation (Journal of Applied Oral Science, 2016)
The knowledge of the internal anatomy of three-rooted mandibular molars may help clinicians to diagnose and plan the root canal treatment in order to provide adequate therapy when this variation is present. Objectives: To determine the prevalence of three-rooted mandibular molars in a Brazilian population using cone beam computed tomography (CBCT) and to analyze the anatomy of mandibular first molars with three roots through micro-CT. Material and Methods: CBCT images of 116 patients were reviewed to determine the prevalence of three-rooted first mandibular molars in a Brazilian subpopulation. Furthermore, with the use of micro-CT, 55 extracted three-rooted mandibular first molars were scanned and reconstructed to assess root length, distance between canal orifices, apical diameter, Vertucci's classification, presence of apical delta, number of foramina and furcations, lateral and accessory canals. The distance between the orifice on the pulp chamber floor and the beginning of the curvature and the angle of canal curvature were analyzed in the distolingual root. Data were compared using the Kruskal-Wallis test (α=0.05). Results: The prevalence of three-rooted mandibular first molars was of 2.58%. Mesial roots showed complex distribution of the root canal system in comparison to the distal roots. The median of major diameters of mesiobuccal, mesiolingual and single mesial canals were: 0.34, 0.41 and 0.60 mm, respectively. The higher values of major diameters were found in the distobuccal canals (0.56 mm) and the lower diameters in the distolingual canals (0.29 mm). The lowest orifice distance was found between the mesial canals (MB-ML) and the highest distance between the distal root canals (DB-DL). Almost all distal roots had one root canal and one apical foramen with few accessory canals. Conclusions: Distolingual root generally has short length, severe curvature and a single root canal with low apical diameter.